Application of Enzymatic Hydrolysis on Sunflower Lecithin Using a Pancreatic PLA2 - Cabezas, Darío Marcelino (2010)
The aim of the present investigation was to evaluate the influence of the main operating conditions on the application of an enzymatic hydrolysis on sunflower lecithin at laboratory scale. This study seeks to contribute to the oil industry with useful information for rescaling this modification process, in order to increase the value-added of sunflower lecithins.